Association Between Subconjunctival Hemorrhage and Acute Coronary Syndrome: A 14-Year Nationwide Population-Based Cohort Study - Chiang, Ping-Hao; Lai, Jung-Nien; Chiang, Yun-Chi; Hu, Kai-Chieh; Hsu, Min-Yen; Wei, James Cheng-Chung (Frontiers in Cardiovascular Medicine, 2021)
Purpose Subconjunctival hemorrhage (SCH) is usually a benign ocular disorder that causes painless, redness under the conjunctiva. However, since SCH and acute coronary syndrome (ACS) share many vascular risk factors, studies have suggested that these two disorders may be significantly associated with each other, and evaluate the concomitance of ACS in patients with SCH. Methods This population-based cohort study, enrolled 35,260 Taiwanese patients, and used the Taiwan National Health Insurance Research Database to identify patients with ACS and SCH. Outcomes were compared between the with and without SCH groups. The study population was followed until the date of ACS onset, the date of withdrawal, death, or December 31st 2013, whichever came first. Results Of the 85,925 patients identified with SCH between 1996 and 2013, 68,295 were excluded based on the study’s exclusion criteria, and a total of 17,630 patients with SCH who were diagnosed by ophthalmologists between 2000 and 2012 were eligible for analysis. After 1:1 propensity score matching for 5-year age groups, gender, and the index year, the results showed that SCH was more common in the 40-59 age group (53.82%) and females (58.66%). As for the ACS-related risk factors, patients with diabetes mellitus (aHR = 1.58, 95% CI = [1.38, 1.81]), hypertension (aHR = 1.71, 95% CI = [1.49, 1.96]) and patients taking aspirin (aHR = 1.67, 95% CI = [1.47, 1.90]) had a notably higher risk of ACS. However, it was found that there were no significant differences in the occurrence of ACS between the non-SCH and SCH patients. Conclusion This results of this study regarding the risk factors and epidemiology of SCH and ACS were in keeping with previously reported findings. However, the results revealed no significant association between SCH and ACS.